2019
DOI: 10.1021/acs.iecr.9b00306
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of S or N-Containing Carbon Segments by Alkalic or Acidic Activators

Abstract: To date, the activation reactions of heteroatom-containing carbon segments have not been systematically studied. Here, activation of S,N dual-doped petroleum coke (SNC) by acidic (CO 2 ), alkalic (KOH and NH 3 ), and neutral (H 2 O) activators is investigated. The reactions between activators and S/N-containing segments are similar to the typical acid−base reactions. SNC exhibits higher activation reactivity as compared to the undoped carbon, thus leading to a high SSA even at low activation temperature. S-Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…All peaks information has been summarized in Table S1. Cao et al [33] reported that AC by CO 2 activation possessed 2.5 at% of N and 5.8 at% of S, which was higher than the AC (2.17 at% N and 0.85 at% S) by KOH activation. It is clear that the physical activation avoid over consuming carbon atoms, benefiting the heteroatoms remain.…”
Section: Physical Properties Of the Materialsmentioning
confidence: 97%
See 1 more Smart Citation
“…All peaks information has been summarized in Table S1. Cao et al [33] reported that AC by CO 2 activation possessed 2.5 at% of N and 5.8 at% of S, which was higher than the AC (2.17 at% N and 0.85 at% S) by KOH activation. It is clear that the physical activation avoid over consuming carbon atoms, benefiting the heteroatoms remain.…”
Section: Physical Properties Of the Materialsmentioning
confidence: 97%
“…Not like the chemical activation, CO 2 activation is a green way to construct AC with micropores through adjusting the flow rate of CO 2 gas, temperature and reaction time [30][31][32] . But the yield of AC could decrease during the CO 2 consumption, and underdeveloped porous structure causes low specific surface area (SSA) of AC [31,[33][34] . Some reports had constructed AC by combining CO 2 activation with KOH activation [35,36] , but the carbon source and activation protocol leave a big unknown to the features of products.…”
mentioning
confidence: 99%